Sovereign Borrowing, Financial Assistance and Debt Repudiation - Florian Kirsch; Ronald Rühmkorf (University of Bonn, Bonn Graduate School of Economics (BGSE), 2013)
Official lenders provide financial assistance to countries that face sovereign debt crisis. The availability of financial assistance has counteracting effects on the default incentives of governments. On the one hand, financial assistance can help to avoid defaults by bridging times of fundamental crises or resolving coordination failures among private investors. On the other hand, the insurance effect of financial assistance lowers borrowing costs which induces the sovereign to accumulate higher debt levels. To assess the overall effect of financial assistance on the probability of default we construct a quantitative model of endogenous credit structure and sovereign default that allows for self-fulfilling expectations of default. Calibrating the model to Argentinean data we find that the availability of financial assistance reduces the number of defaults that occur due to self-fulfilling runs by private investors. However, at the same time it raises average debt levels causing an overall increase of the probability of default.
Keywords: F34; G15; O19; 330; Sovereign debt; Sovereign default; Self-fulfilling runs; Bailout